Longitudinal Associations between Physical and Relational Victimization and Student Academic Achievement in Early Adolescence: A Cross-lagged Panel Study - Chen, Liang (Best Evidence in Chinese Education, 2023)
Academic Acadjustments and peer relationships are two crucial aspects of adolescent school adaptation. Peer victimization is a risk factor in student academic achievement; at the same time, poor academic performance can potentially cause peer victimization. With peer victimization, individuals experience aggressions from peers, which can be physical or relational. Physical victimization refers to their being physically attacked by peers, such as being hit, pushed, and kicked; in relational victimization, they are subjected to non-physical attacks, such as social exclusion and rumor dissemination.